Language Variation Sociolek In Batak Toba Movie “Ilu Na Maraburan” Directed By Bonardo Sinaga - Sri Rezeki Hutagalung; Nurhayati Sitorus; Harpen Silitonga; Sarma Pangabean (Journal on Education, 2023)
The aims of this study is to find out the types of language variations as part of sociolinguistics. Here the focus of the study is language variation. This study used qualitative descriptive as approach and research design is an observation analysis. The source data were Ilu Na Maraburan movie script by Bonardo Sinaga taken from internet. This study based on Wardhaugh in all update theories. The research found that there were four types of language variations used in Ilu Na Maraburan movie by Bonardo Sinaga. From totally 41 sentences, idiolect is 9, dialecti is 13, chronolect is 8, and social dialect is 11. It shows that the movie mostly dominant used the Dialect with 13 the percentage (31,7%). (1) for the student of the English Department, this study can increase knowledge about language variations, especially for anyone who likes to watch movie. Understanding language variation is very important because there are many language variations contained in the movie. (2) For the lecturer who act as educators, this study will be useful to enrich their knowledge and added their knowledge about language variations and lecturer can teach language variation with the newest references. (3) For other researcher, this study is expected or even able to provide new refences when conducting research in different perspective.